Validation of self-reported incident cardiovascular disease events in the Greek EPIC cohort study (Italian Journal of Public Health, 2012)
Background: the aim of the study is to investigate the validity of self-reported incident cardiovascular disease in the Greek EPIC cohort during follow up.Methods: cardiovascular disease was considered in 4 groups: Myocardial infarction (MI), Angina, Cerebrovascular disease, and other coronary heart disease (other CHD). Validation for all reported incident cardiovascular events was sought through medical records of hospitals around the country and local death registries.Results: in total, there had been 121 self reported incident cases of angina, 683 of MI, 622 of other CHD and 855 of cerebrovascular disease. Records were searched for 926 participants with reported cardiovascular disease (CVD), and from those, medical records for the 832 (90%) were obtained from the respective hospitals. Examination of the medical records that were obtained confirmed the self report in 72% of incident strokes, 65% of MIs, 55% of other CHD cases and 32% of angina.Conclusions: it appears that in our study self reported MI and stroke (or transient ischemic attacks) had a higher validity, compared to self reported angina and other CHD. Our results are comparable to those in other cohort studies.
Keywords: Cardiovascular; Cohort; Validation; Self-reported; Myocardial infarction; Stroke